Studi Filosofis terhadap Metode dan Aksentuasi Pendidikan Islam Organisasi Muhammadiyah dan Nahdlatul Ulama - Hanifatun Jamil; Mega Aulia Suwitno; Utami Qonita Rahmi (Universitas Islam Lamongan, 2025)
Islamic education in Indonesia possesses distinctive characteristics, particularly reflected in the contributions of two major organizations, Muhammadiyah and Nahdlatul Ulama (NU). This article examines the philosophical differences in educational methods and emphases between Muhammadiyah and NU, as well as their impact on the dynamics of Islamic education in Indonesia. The research employs a literature study with a descriptive-qualitative approach. The analysis reveals that fundamental philosophical differences shape variations in educational orientation, achievements, and dynamics. Muhammadiyah advances a progressive model of education grounded in modern science and technology, emphasizing rationality, innovation, and adaptability to global developments. In contrast, NU sustains a traditional approach through the pesantren system, rooted in the study of classical Islamic texts (kitab kuning), spiritual values, etiquette, and strong teacher–student relationships. Despite these differences, both organizations complement one another and collectively enrich the landscape of Islamic education in Indonesia.